1983
DOI: 10.1128/mcb.3.8.1412
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a phosphorylated form of calmodulin in chicken brain and muscle.

Abstract: Phosphocalmodulin (PCaM) was identified after analysis of calmodulin (CaM) preparations by two-dimensional gel electrophoresis by using a modified ampholyte system to resolve very acidic proteins. The analysis of CaM prepared by the conventional procedure based upon its heat resistance and acidity as well as the analysis of whole urea extracts from brain showed that PCaM was a major component in this tissue. PCaM was 1 pH unit more acidic than CaM, and its electrophoretic mobility, unlike CaM, was not changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 36 publications
0
37
1
Order By: Relevance
“…CaM is more efficiently phosphorylated at serine/threonine than at tyrosine residues in living cells [47][48][49]. Thus, to determine whether P-(Tyr)-CaM could be involved in the EGF-dependent activation of the EGFR, we set to assay in vitro the isolated EGFR from rat liver and A431 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CaM is more efficiently phosphorylated at serine/threonine than at tyrosine residues in living cells [47][48][49]. Thus, to determine whether P-(Tyr)-CaM could be involved in the EGF-dependent activation of the EGFR, we set to assay in vitro the isolated EGFR from rat liver and A431 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Testing the effect of P-(Tyr)-CaM on EGFR activation in living cells is a challenging task, since the amount of P-(Tyr)-CaM in most non-transformed cells and tissues appears to be very low or undetectable, in contrast with the more abundant P-(Ser/Thr)-CaM species [47][48][49]. We therefore tested the effect of P-(Tyr)-CaM on the EGFR using an in vitro assay system.…”
Section: Egfr-phosphorylated Cam Enhances Egf-dependent Egfr Activationmentioning
confidence: 99%
“…Recently we have demonstrated that the epidermal growth factor (EGF) receptor can be isolated by calmodulin-affinity chromatography, and that calmodulin inhibits its tyrosine lunase activity (San JosC et al, 1992). Calmodulin, therefore, could potentially play a regulatory role in the EGF-mediated mitogenic-signal pathway.Calmodulin has been shown to be a substrate for several different protein kinases (Plancke and Lazarides, 1983 ;Hiiring et al, 1985;Fukami et al, 1985;Graves et al, 1986;Lin et al, 1986;Nakajo et al, 1986Nakajo et al, , 1988Meggio et al, 1987Meggio et al, , 1992Kubo and Strott, 1988;Sacks and McDonald, 1988;Laurino et al, 1988; Sacks et al, 1989aSacks et al, , 1992aSan JosC et al, 1992;Benguria et al, 1993;Saville and Houslay, 1994). Since this phosphorylation process occurs in intact …”
mentioning
confidence: 99%
“…cells (Plancke and Lazarides, 1983;Fukami et al, 1985;Nakajo et al, 1986;Colca et al, 1987;., 1992b), phosphocalmodulin could play an important role in the physiology of the cell. In support of this, it has been shown that phosphorylation of calmodulin by casein kinase-2 (an insulin-sensitive and EGF-sensitive serinehhreonine kinase) alters the biological activity of calmodulin by decreasing the activation of two calmodulin-dependent enzymes, myosinlight chain kinase and cyclic-nucleotide phosphodiesterase (Sacks et al, 1992a).…”
mentioning
confidence: 99%
“…We have demonstrated previously that PKC-mediated phosphorylation of KCNQ2 subunit regulates KCNQ2-CaM binding (7). Interestingly, 15-40% of endogenous CaM is known to be phosphorylated (8,9), although the functional role of phosphorylated CaM on KCNQ2 channel remains unknown. Protein kinase CK2 (casein kinase 2) has been identified as key kinase for phosphorylating CaM (10,11).…”
mentioning
confidence: 99%